2008
DOI: 10.1088/0031-8949/77/03/035302
|View full text |Cite
|
Sign up to set email alerts
|

Kündig's experiment on the transverse Doppler shift re-analyzed

Abstract: In this paper, we re-analyze the ingenious experiment by Kündig (measurement of the transverse Doppler shift by means of the Mössbauer effect) and show that a correct processing of experimental data gives a relative energy shift E/E of the absorption line different from the value of classically assumed relativistic time dilation for a rotating resonant absorber. Namely, instead of the relative energy shift E/E = −(1.0065 ± 0.011)v 2 /2c 2 reported by Kündig (v being the linear velocity of absorber and c being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
118
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(126 citation statements)
references
References 10 publications
7
118
1
Order By: Relevance
“…The values for a m which agree within these errors are three orders of magnitude larger than the value of 1 · 10 19 m/s 2 derived from the rotor experiments [20], [21], [22]. At low temperatures…”
Section: Measurements Onsupporting
confidence: 64%
“…The values for a m which agree within these errors are three orders of magnitude larger than the value of 1 · 10 19 m/s 2 derived from the rotor experiments [20], [21], [22]. At low temperatures…”
Section: Measurements Onsupporting
confidence: 64%
“…79 065007), and once again strongly pointed to the inequality k>0.5, revealed originally in (A.L. Kholmetskii et al 2008 Phys. Scr.…”
mentioning
confidence: 52%
“…At the same time, the uncertainty in the determination of k in our experiment is still 3.5 times larger, than the measurement uncertainty of Kündig experiment, as we reanalyzed (ref. [10]). Such is the cost, which we have paid for the elimination of influence of vibrations via the data processing procedure with two different resonant absorbers (we remind that in the Kündig experiment, the influence of vibrations had been eliminated at the instrumental level).…”
Section: Experiments and Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…In [1] they found that the original experiment by Kündig [3] contained errors in the data processing. A puzzling fact is that, after correction of the errors of Kündig, the experimental data gave the value [1] …”
Section: Introductionmentioning
confidence: 99%